Efektivitas Penggunaan Game Edukasi di Sekolah Dasar: Sistematis Literatur Review - Yovita Yovita; Winda Fajar Qomariah; Alaniyah Syafaren (Milenial: Journal for Teachers and Learning, 2022)
The low knowledge of teachers about the learning media needed in learning during the COVID-19 pandemic as well as the 21st century greatly affects learning media. So this study aims to determine the type of educational game-based learning media in the learning process in elementary schools and the effectiveness of the use of educational game-based learning media used in the learning process in elementary schools. The method used is systematic literature (Systematic Literature Review) using PRISMA diagrams. The database used to search for literature uses two digital libraries, namely Harzing, WOS, Google Scholar and Garuda. In order for the selected literature to be relevant, use the keyword “Game education”. The next step is to search for scientific article publications from 2016 to 2021 which discuss the use of educational game-based learning media in the learning process in elementary schools. The results of the search for scientific articles contained 17 articles that would be analyzed and synthesized. The analytical technique used is the narrative method by grouping the extracted data. The result of this research is that educational games can be developed and applied to various fields of study or subjects using Experimental and R&D methods. when applying educational games using Experiments and when you want to innovate, you can use the R&D research method.